Program for the development of digital competencies in teachers of the Stomatology career. Isla de la Juventud - Ivonnet-Gutiérrez, Ennis; Peña-Méndez, Aliana; Silva-Vázquez, Felicia; Zaldívar-Carmenate, Leonides; Vargas-Labrada, Luisa Sucel (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: information and communication technologies are important tools for training and communication. To facilitate their work in the educational system as a requirement for change in the profile of the education professional, teachers must develop suitable digital skills to implement in their teaching-learning process.Objective: design a program for the development of digital skills in teachers of the Stomatology career of the Faculty of Medical Sciences of the Isla de la Juventud, 2022.Methods: a descriptive study was carried out, from a methodological perspective based on the qualitative paradigm. The universe was made up of 150 teachers, of which 40 made up the sample. The theoretical level research methods were used: analytical-synthetic, inductive-deductive and historical-logical analysis; at the empirical level: documentary analysis, survey and specialist criteria.Results: the need to train the teaching staff and guide the preparation of teachers in the appropriate use of computer techniques and resources, as well as in the preparation and development of virtual courses using the Moodle platform, was confirmed.Conclusions: information and communication technologies are fundamental in the teaching-learning process. The development of digital competencies in teachers shows a low level of performance; the expressed limitations focus mainly on knowledge and domains in content creation, communication and collaboration.